Unveiling the vortex glass phase in the surface and volume of a type-II superconductor - Aragón Sánchez, J. (2019)
Fil: Aragón Sánchez, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina